Multifunctional Polarization Converters Based on Linear-to-Circular Polarization Decomposition Reflective Surfaces - Zhang, Tao; Wang, Haoran; Peng, Chongmei; Chen, Zhaohui; Yang, Guo-Min; Wang, Xiaoyi (IEEE transactions on antennas and propagation)
This article proposes a novel design strategy to realize multifunctional reflective surface polarization converters based on the concept of linear-to-circular polarization decomposition. By decomposing the linearly polarized incident wave into a pair of orthogonal circularly polarized waves, namely, a right-handed circularly polarized (RHCP) wave and a left-handed circularly polarized (LHCP) wave, and controlling the phase states of the two circularly polarized components independently, various polarization conversion functions may be achieved. A reflective surface unit cell consisting of a square patch and a 90° hybrid coupler is proposed to facilitate the linear-to-circular polarization decomposition, allowing to adjust the phase states of the two circularly polarized components by adding different phase shifters at the end of the hybrid coupler. Three different functions including linear-to-dual-polarization conversion, simultaneous linear polarization rotation and beam steering, and radar cross section (RCS) reduction are realized based on the proposed reflective surface unit cell. The proposed design strategy is theoretically analyzed and demonstrated by three reflective surfaces corresponding to the three functions with both full-wave simulation and experiment.